PERAN KELOMPOK USAHA WISATA DALAM PENYEDIAAN FASILTAS WISATA DI DESA COLO, KABUPATEN KUDUS - Deny Aditya Aditya Puspasari (UNHI Press, 2021)
The tourism sector is one of the approaches in the economic sector which plays an important role in alleviating poverty in a region. Facilities and infrastructure as the supporting factors in tourism development, so that tourism activities can run well. Colo tourist village located in the Muria Mountains area as one of the growing tourist destinations. Regarding to this potential, the village community manages tourism objects independently and informally through the formation of tourism support communities such as motorcycle taxis, lodging entrepreneurs and street vendors. The purpose of this study is to identify the role of these business groups in providing facilities and infrastructure to support tourism activities in Colo Village. Data regarding this role were obtained from the Kudus Regency government institution as well as interviews with the tourism group actors. The results of this study show that the role of tourism groups is very important in providing supporting facilities for tourism activities, so that tourists will be encouraged to come.